Draft Genome Sequence of Ciprofloxacin and Ceftriaxone Resistant Campylobacter jejuni MM26-781 Assigned to Novel ST Isolated From Common Pigeon in Lithuania. (September 2019) - Aksomaitiene, Jurgita; Ramonaite, Sigita; Novoslavskij, Aleksandr; Malakauskas, Mindaugas; Kudirkiene, Egle
Campylobacter jejuni is an important zoonotic pathogen known to be resistant to a wide range of antibiotics worldwide. Campylobacter jejuni may be intrinsically resistant to antibiotics or can acquire antibiotic resistance determinants through gene transfer. However, the knowledge of molecular mechanisms of antimicrobial resistance among Campylobacter isolates from wild birds, especially in Lithuania, is limited. Whole genome sequencing (WGS) is a tool for better understanding the evolutionary and epidemiologic dynamics of C jejuni . This study describes a draft whole genome sequence of C jejuni MM26-781 isolated from a common pigeon ( Columba livia ) in Lithuania in 2011 and assigned to ST-6424 (CC179) sequence type. The draft genome sequence contained 1.68 Mb, comprising 1651 coding genes, 40 transfer RNAs, 1 ribosomal RNA, and 69 pseudogenes with an average G + C content of 30.4%. The RAST (Rapid Annotation using Subsystem Technology) pipeline annotated (NCTC11168) a total of 305 subsystems in the genome of C jejuni MM26-781 strain, with most of the genes associated with amino acids and derivatives related to metabolism (18.93%) and protein metabolism (14.43%). The genes and mutations related to antibiotic resistance, including gyrA and gyrB genes associated with quinolone resistance, blaOXA-448 gene (locus tag C9371_07715) associated with resistance to β-lactams, rpoB gene associated with resistance to rifamycin, vgaE gene associated with resistance to streptogramin and efflux system CmeABC ( cmeA, cmeB, cmeC), efflux pump PmrA, and transcriptional regulator CmeR responsible for multidrug resistance in C jejuni MM26-781 chromosome, were identified. Also, the virulence factors, including ciaB, cadF, ceuE, pldA, motB, and bd1A genes, were identified by WGS data analysis.